Construção e validação do SAMBA: novo método avaliativo de habilidades microcirúrgicas de aneurisma não roto da artéria cerebral média - Taise Miriam Cruz Mosso Ramos (2017)
Introduction: Surgical performance evaluation was first described with OSATS and modified for aneurysm microsurgery simulation by OSAACS. These methods rely in subjective evaluator´s opinion therefore an objective evaluation of proficiency in microsurgery of brain aneurysm has not been reported. Objective: The objective of this study is to describe and validate a score of skills acquisition assessment for microsurgery of brain aneurysm (SAMBA) that can be used similarly in a simulator and in middle cerebral artery non-ruptured aneurysm. Methods: SAMBA was developed and validated though face, inter-rater and testretest reliability using 4 experts, 4 intermediates and 4 beginners performing nonruptured MCA aneurysm microsurgery and ex vivo brain aneurysm surgical simulation. Results: SAMBA results were confronted using descriptive statistics, Croncbach´s alpha indexes and MANOVA analyses (p<0.05). SAMBA results showed that experts, intermediates and novices scored, respectively, an average of 33.9, 27.1 and 16.4 points in real surgery, and 33.4, 27.3 and 19.4 points in simulator. SAMBA inter-rater reliability index for real surgery and simulated surgery were 0.995 and 0.996; intra-rater reliability was 0.983 (Cronbach´s alpha). Averagepoints among expert, intermediate and novice were different in aneurysmmicrosurgery and in simulator (p<0.001). Novice scores were more diverse. Conclusion: Placenta brain aneurysm simulator has been predictive validated, but SAMBA adds to it an objective scoring system to verify microsurgical ability in this complex operation, stratifying by points the proficiency level. SAMBA can be used as an interface between learning and practicing as is can be applied in a safe and controlled environment, such as simulator, with similar results obtained in real surgery.Key Words: Aneurysm; Simulation; Placenta; Evaluation; Craving; Efficiency.